Student’s experience, satisfaction and barriers of hybrid undergraduate obstetrics & gynaecology teaching during Covid-19 pandemic - Basri, Nurul Iftida; Dasrilsyah, Rima Anggrena; Mohd Jamil, Amilia Afzan; Abdul Hamid, Habibah; Md Pauzi, Siti Farhana (Universiti Putra Malaysia, 2022)
Introduction: Hybrid teaching method has been implemented in majority of medical schools to adapt with the Covid pandemic era. With this integrated method, we aim to determine the student’s experience, satisfaction and barriers of hybrid undergraduate teaching in obstetrics & gynaecology posting. Methods: A cross sectional study was conducted among medical students undergoing hybrid teaching during obstetrics & gynaecology posting in the year of 2020 and 2021. Participants were 112 fourth and fifth year medical students whom were affected by the pandemic. Online questionnaires through Google forms were distributed to all eligible students. The questionnaire consists of four sections: socio-demographic, experience, satisfaction and barriers. Results: The response rate was 75%. Majority (90.2%) of the respondents were satisfied with the hybrid teaching. Among the barriers that sometimes encountered by our students were inability to adjust learning style, lack of technical skills, mental health difficulties, emotional difficulties, unreliable internet access and an unconducive study environment. Among all the demographic data studied, only ethnicity showed a significant association with the satisfaction of the students. Conclusion: Our study found that majority of students were satisfied with hybrid teaching with minimal barriers experienced. Hence its practice can be continued as it can be utilised at any time as compared to traditional teaching.